Angiotensin ii- and vasopeptidase-inhibitory activities of gynura procumbens / Poh Ting Fung - Poh , Ting Fung (2014)

(untitled)
Blood pressure (BP) is partly determined by vasoconstriction or vasodilation. The most important vasoconstrictor is angiotensin II (Ang II) whilst nitric oxide (NO), prostacyclin (PGI2) and bradykinin (BK) are main vasodilators. The vasopeptidase, angiotensin-converting enzyme (ACE), is able to hydrolyse BK and convert angiotensin I (Ang I) to Ang II. Bradykinin is also inactivated by another vasopeptidase, neutral endopeptidase (NEP). Increases in ACE and NEP activities would elevate Ang II but decrease BK levels that could cause increases in BP which in the long-term could result in hypertension. Many antihypertensive drugs are available but with side-effects. Alternative forms of treatments, especially those from the plant kingdom, are frequently sought after. Gynura procumbens (G. procumbens) is widely used in folk medicine to treat hypertension. Previous findings show that leaves of this plant seem to decrease BP by inhibiting ACE activity and blocking calcium channels. The aims of this project are to further study the BP-lowering properties of this plant by exploring the Ang II and ACE/NEP inhibitory activities of a partially purified fraction (FA-I) and to characterise the bioactive subfractions. Endothelium-intact and -denuded rat aortic rings suspended in organ chambers were used to study the effects of FA-I on Ang I- and Ang II-induced contractions. The role of endothelium on the effects of FA-I was tested further by adding Nω-nitro-L-arginine methyl ester (L-NAME) or indomethacin to ascertain the involvement of NO and PGI2 respectively. Effects of FA-I on the vasodilatory response due to BK were studied by in vitro and in vivo methods. Rats were also given oral doses of FA-I to examine the stability of the fraction against digestive enzyme degradation. The FA-I fraction was subjected to further separation by thin layer chromatography (TLC) to obtain the FA-I subfractions, the iv activities of which on ACE/NEP were analysed by spectrophotometric and spectrofluorometric assays. After 1H-nuclear magnetic resonance analysis, one of the bioactive subfractions was sent for further structural characterisations. Results show that FA-I significantly (p<0.05) decreased the contraction evoked by Ang I and Ang II in endothelium-intact and -denuded rings with the degree of relaxation being significantly (p<0.05) higher in intact ones. However, in the presence of L-NAME or indomethacin, the inhibitory effect of FA-I on Ang II-induced contraction was significantly (p<0.05) reduced. In contrast, FA-I enhanced the vasorelaxant effects of BK, which may contribute to the greater BP-lowering effects of BK. Activities of ACE and NEP was inhibited by FA-I. Early-eluted subfractions obtained from TLC exhibited specific inhibition on ACE alone. Study also shows that the ACE inhibitory activity of FA-I was still preserved after the actions of proteases and spectral analyses showed that FA-I subfractions may contain 16-carbon compounds. In conclusion, FA-I was found to be able to inhibit Ang II-induced contractions, probably via endothelium-dependent pathways by activating NO or PGI2 release, and also of being able to inhibit ACE/NEP activities. Nuclear magnetic resonance and mass spectroscopic analyses indicate that one of the subfractions (FA-Ia) could be a 16-carbon compound but the precise structure remains to be elucidated.